Students’ Perceptions Toward The Use of Kahoot! Online Game for Learning English - Bambang Widi Pratolo; Tio Moon Lofti (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aims to determine students' perceptions of using Kahoot! in learning English, the problems on the use of Kahoot! In learning English faced by students. This study used a qualitative research approach, and the subjects of this study were 10 students of the Ahmad Dahlan University of English Language Education. Data were collected using the open-ended interview as the instrument. Data analysis in this study used a qualitative descriptive. In analyzing data, this study refers to coding analysis consisting of data reduction, data presentation, and conclusion drawing. This research revealed that the benefits of using Kahoot! as follow: (1) motivating students to learn, (2) building a good atmosphere in class, (3) helping students to get focus, and (5) providing positive competition. The problem of using Kahoot! includes (1) unstable internet connection, and (2) the absence of space for students and teachers to discuss.